DISKURS TUSHUNCHASI VA CHET TILI KOMMUNIKATIV KOMPETENSIYASINI SHAKLLANTIRISHNING PEDAGOGIK USULLARI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article, the opinion of scientists and pedagogues on the scientific- theoretical basis of the factors of the development of oral speech in students, the use of new pedagogical methods, in particular, interactive methods in teaching French opinions, scientific views were analyzed and a subjective attitude was expressed to them.
Keywords: interactive methods, role-playing games, brainstorming, case-study, innovations, intellectual games.